Colonizing prescriptions and possible overflows on the history curriculum - Silva, Guilherme Henrique da; Lucini, Marizete (Práxis Educacional, 2022)
This article’s objective is to present reflections in the context of History Teaching in dialogue with scenarios experienced in the exercise of teaching, in the discipline of History, in a public school in the state of São Paulo, in the context of the pandemic caused by SARS-CoV-2, in remote teaching modality. To do so, we anchored urselves in reports collected during classes and bibliographic studies, in the field of curriculum studies and History teaching. This teaching practice made possible problematizations between the content offered in line with the official guidelines and its unfolding amongst the students. Faced with the relationship between the official curriculum and students, the central question of this work emerged: to discuss the place of the Other and the Difference in the São Paulo curriculum during the pandemic. In the end, these implications direct us to reflect on how a problematized education alters not only the teaching practices, but also the student's profiles, reflecting in a democratic society.